Informality in global South cities: Case studies of Kuala Lumpur and Rio De Janeiro / Luiza Farnese Lana Sarayed-Din - Luiza Farnese Lana, Sarayed-Din (2017)
Global south cities, particularly those suffering a recent booming urbanization, have been in desperate need of urban interventions able to address their deeply rooted inequality. The traditional planning practices have shown their inadequacy of such realities and exposed the importance of an urban practice compromised with different ways of looking at informality within global south cities. The main question that this thesis explores is what are the other ways of addressing informality in global south cities’ urban planning practices? Delving deeply into this question, this study broadens the very term “informality”. In order to do that, it reviews the literature associated with both the traditional modernist way of looking at informality as well as the one that critically assessed the structural nature of informality as a strategy of planning. In doing so, the theoretical framework of this thesis is depicted by identifying three critical elements of informality in global south cities, namely history, power and people’s relation. Framed by such critical elements and embedded in a social constructivist approach, this thesis, then, investigates two historical inhabited urban areas under the pressure of development located in two global south cities: Kuala Lumpur and Rio de Janeiro. The case studies of both cities offer, in turn, empirical confirmation of those three critical elements of informality, revealing the implication of modernist urban practices; single accounts of history; state power; market forces; traditional lifestyle handling and stakeholder participation, on the very production of global south cities’ urban crisis. Following that and moving away from the idea of informality as an issue of poverty, this thesis proposes an analytical framework of informality in global south cities, particularly looking into informality in a fractal fashion. As a contribution to scholarship in urban planning, this thesis offers an analytical framework of informality in global south cities. This framework, in turn, supports the required diagnostic effort of planners involved in addressing global south cities’ challenges, as well as provides more subsidies for the theoretical development of this growing field of knowledge.